INFLUENCE OF TEMPERATURE AND RAINFALL ON THE HELMINTH INFECTION IN A FRESHWATER CAT FISH, MYSTUS BLEEKERI DAY, 1878 - RAO, S. MANOHAR; RAO, V RAJESHWARA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1991)
The temperature and rainfall affected the helminth parasitic population in the host. The high temperature and low rainfall favoured the increase of incidence of infection and low temperature and high rainfall had an adverse effect on the infection levels of helminths of freshwater catfish, M. bleekeri.